2013
DOI: 10.3389/fpsyg.2013.00291
|View full text |Cite
|
Sign up to set email alerts
|

Invisible emotional expressions influence social judgments and pupillary responses of both depressed and non-depressed individuals

Abstract: We used filtered low spatial frequency images of facial emotional expressions (angry, fearful, happy, sad, or neutral faces) that were blended with a high-frequency image of the same face but with a neutral facial expression, so as to obtain a “hybrid” face image that “masked” the subjective perception of its emotional expression. Participants were categorized in three groups of participants: healthy control participants (N = 49), recovered previously depressed (N = 79), and currently depressed individuals (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
(53 reference statements)
3
24
0
Order By: Relevance
“…All these results seem to lend support to our finding, according to which the subliminal processing of emotions influences the observers' responses, as Laeng et al . (, ) proposed by using hybrid faces. However, an fMRI study (Pessoa, McKenna, Gutierrez, & Ungerleider, ) suggested that the processing of facial expression, which involves cortical and subcortical structures, can be performed only with a sufficient level of attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these results seem to lend support to our finding, according to which the subliminal processing of emotions influences the observers' responses, as Laeng et al . (, ) proposed by using hybrid faces. However, an fMRI study (Pessoa, McKenna, Gutierrez, & Ungerleider, ) suggested that the processing of facial expression, which involves cortical and subcortical structures, can be performed only with a sufficient level of attention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paradigm that has been helpful in understanding implicit processing of face information is that of ‘hybrid faces’ (Schyns & Oliva, ), in which different facial information are superimposed within different ranges of spatial frequencies. In this paradigm, the image of a face with an emotional (positive or negative) expression is typically low‐pass filtered and superimposed to a high‐pass filtered neutral face (Laeng et al ., , ; Leknes et al ., ; Prete, Laeng, & Tommasi, ). Laeng and colleagues asked participants to judge (on a 5‐point Likert scale) how friendly the face of the same individual appeared in different hybrid stimuli displaying the basic emotions only in the low spatial frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Pupillographic measurements have been previously used to indirectly track the activity of LC neurons ( Silvetti et al, 2013 ; Hoffing and Seitz, 2015 ; Kihara et al, 2015 ; Hayes and Petrov, 2016 ; see also Laeng et al, 2013 ; De Cicco et al, 2014 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the LC neurons activity is strongly and positively correlated with the pupil size, both in animals ( Rajkowski et al, 1993 , 1994 ; Joshi et al, 2016 ) and humans ( Alnaes et al, 2014 ; Murphy et al, 2014 ). For this reason, several studies have utilized the pupil size as an index of LC activity ( Silvetti et al, 2013 ; Hoffing and Seitz, 2015 ; Kihara et al, 2015 ; Hayes and Petrov, 2016 ; see also Laeng et al, 2013 ). The connection of the trigeminal system with the ARAS and LC suggests that the modifications of trigeminal input occurring during chewing may induce relevant changes in the whole brain, leading to an enhancement in the arousal/alertness level and, as a consequence, in the cognitive performance ( Sakamoto et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Affective pictures or sounds, mainly representing violence and erotica, have been shown to robustly increase SCRs and pupil dilations of the perceiver (Partala and Surakka, 2003;Bradley et al, 2008;Lithari et al, 2010). While the processing of emotional expressions has been shown to evoke emotion-related pupil size changes (see Kuchinke et al, 2011 for prosodic stimuli, Laeng et al, 2013 for faces), evidence for increased SCRs to emotional expressions is, however, less clear (Alpers et al, 2011;Aue et al, 2011;Wangelin et al, 2012). Alpers et al (2011) and Wangelin et al (2012) directly compared SCRs to emotional faces and affective scenes.…”
Section: Introductionmentioning
confidence: 99%